Recycling Words, Repairing Talk: A Corpus–Conversation Analysis of Active Learning in Papua - Rizdika Mardiana; Nurrahma Restia Fatkhiyati; Mukhamdanah Mukhamdanah; Bambang Nur Alamsyah Lubis; Sri Sumarni; Sudarya Permana (STAIRS: English Language Education Journal, 2026)
This study examines student discourse in an English classroom at a senior high school in Papua, Indonesia, through an integrated framework combining corpus linguistics and Conversation Analysis (CA). The research aims to (1) characterize students’ spoken output in active learning settings, (2) determine the extent to which their utterances reflect authentic and communicative English use, and (3) provide corpus-informed pedagogical insights tailored to learners’ linguistic needs. Data were collected via classroom observations, audio–video recordings, transcriptions of teacher–student interactions, and semi-structured interviews. A mini spoken corpus was developed to analyze lexical frequency, collocational tendencies, and formulaic expressions, while CA was employed to examine sequential organization, turn-taking, adjacency pairs, and repair mechanisms. The analysis revealed that student utterances were largely short, formulaic, and lexically concentrated around thematic items such as invitation, party, and birthday. Frequent formulaic sequences, including I would like… and I hope you are coming to my birthday party, facilitated learners’ fluency and extended participation. CA findings further indicated that teacher-controlled turn-taking and repair sequences played a crucial role in scaffolding learner output and promoting interactional competence. Overall, the integration of corpus and CA methodologies illuminates the interplay between lexical development and interactional structure in classroom discourse. The study concludes that active learning environments, when coupled with data-driven insights, can enhance both communicative authenticity and linguistic accuracy, offering valuable implications for EFL pedagogy in under-researched contexts such as Papua.